Another Cryptogram in "Shakespeare’s" Dedication to His Sonnets - Walach, Harald (Journal of Scientific Exploration, 2021)
I read with great interest the paper by Peter Sturrock and Kathleen Erickson (Sturrock & Erickson, 2020) on the Dedication in Shakespeare’s Sonnets. I am neither a scholar of literature, nor of Shakespeare, and I do not want to enter the fray as to who was the author of Shakespeare’s sonnets and plays. But I must confess that I found the arguments presented by Sturrock and Erickson intriguing. It is in that vein I would like to communicate an interesting finding. On page 302, Figure 21, of their paper, they present the Dedication of the Sonnets as a grid of 12 x 12 letters. This was done under the assumption that cryptograms can be deciphered better if they are laid out in a certain format. They then present the message they assume is contained there: “PRO PARE VOTIS EMERITER” as a devotion of Edward de Vere, the Earl of Oxford to his supposed friend, the Earl of Southampton, Henry Wriothesley. I find this a possible meaning. My experience with Latin texts – based on a translation of a medieval mystical writer from Latin into German and the reading of many original Latin texts, mainly from the middle ages and beyond (Hugo de Balma, 2017; Walach, 1994, 2010) – let another sequence jump out at me: SI PATET PRO MIRE VERO RETIRO The translation would read: "If it becomes miraculously obvious [who I am], I retire." That this is a reference of the proposed author, Edward de Vere, to himself would become clear from the double use of “vero”.